Optimalisasi Peran Pendamping Pph Halal Center Uin Saizu Dalam Sertifikasi Halal Dan Pengembangan Ekosistem Halal Banyumas - Miftaakhul Amri (Universitas Islam Negeri Sumatera Utara, 2025)
The purpose of this study is to analyze the optimization of the role of PPH Companions in the halal self-declare certification process and the development of the halal ecosystem in Banyumas. The research method used in this study is field research. This study uses a qualitative approach to case studies. This research conducted interviews with Halal Product Assistants and MSEs, meaning that researchers carefully, thoroughly and deeply know the role of PPH Companions in the halal self-declare certification process and the development of the halal ecosystem in Banyumas. The results of this study indicate that the PPH Halal Center UIN SAIZU Companions have assisted many MSEs in submitting halal certification applications, which in the assistance process have been in accordance with the established procedures. There are several opportunities obtained from the assistance process, but there are still several obstacles in it. With this optimization effort, it is hoped that it can resolve the obstacles faced so that assistance for MSEs in submitting halal certificates in Banyumas becomes more optimal so that it can develop the halal ecosystem in Banyumas